ThinkDeeper Web Coach: A Literature-Informed Design Specification for Process-Visible Reasoning in Problem-Solving-Intensive Information Technology Courses - Rafli Arrasyid; Nuur Wachid Abdul Majid (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2026)
Information technology education increasingly requires students to demonstrate how they reason while generative tools can produce plausible code, queries, and explanations with little visible evidence of the learner's own computational thinking. This study aimed to design ThinkDeeper Web Coach, a process-visible learning artifact for problem-solving-intensive IT courses that requires structured reasoning before direct solution support is accessed. A literature-informed design and development approach was applied to academic records indexed in Semantic Scholar and OpenAlex. The evidence corpus comprised 500 records published from 2023 to 2025, 130 records retained after abstract screening, 53 full texts assessed, and 51 studies included after full-text screening and extraction. The synthesis produced the Process-Visible Learning Design Framework, eight evidence-linked design requirements, and six integrated modules: Answer Delay Gate, Coach Chat, Evidence Drawer, Depth Analytics, Learning Circle, and Resource Recommendation. The revised specification defines applicable course contexts, operational dimensions of depth of thinking, a hybrid reference architecture, server-side gate and guardrail mechanics, trace data objects, and a staged evaluation protocol. ThinkDeeper is presented as a theoretically and empirically justified design specification that still requires expert review, usability testing, trace validation, and classroom pilot evaluation before effectiveness claims can be made.